Estudo e modelagem 3D de um cabeçote para um motor monocilíndrico, 400cc, 4 T - Bruni, Paulo Henrique de Melo [UNESP] (2011)
The cylinder head contains the combustion chamber for the air-fuel mixture and the intake and exhaust valves, the valve guide and the valve seat. The cylinder head also is a support for the camshaft and valve rocker. The holes where the spark plugs are connected are designed to fit the better place in the combustion chamber. The cylinder heads often are manufactured using materials such as aluminum and cast iron. The cooling fins located in the outside of the cylinder head are designed for a good heat transfer and therefore their dimensions and positioning are important. This work aims the calculation for a cylinder head to be installed in a 400 cc displacement, gasoline powered, four stroke, single cylinder engine. According to the displacement it will be analyzed the combustion chamber, the intake and exhaust valves, as well as the camshaft and rocker arms. This also a work to help to accomplish the design of a single cylinder engine, where the alternatives parts, cylinder block and crankcase are all already machined and assembled in this campus